Engineering one-dimensional hollow beta-In2S3/In2O3 hexagonal micro-tubes for efficient broadband-light photocatalytic performance. Issue 9 (11th February 2022) - Shen, Qiuyan; Zhou, Shuo; Yang, Feng-Lei; Wang, Xiaojun; Han, Xiguang
Abstract : Tubular-hexagonal beta-In2 S3 /In2 O3 heterojunctions with a porous shell encapsulated by N-doped carbon, show excellent performance towards photocatalyzing the coupling of amines to imines. Abstract : Improving the utilization efficiency of visible sunlight and improving the separation efficiency of photogenerated carriers are two important factors that enhance the catalytic activity of a photocatalyst. In this article, a tubular-hexagonal beta (β)-In2 S3 /In2 O3 heterojunction with a porous shell encapsulated by N-doped carbon was prepared under a controlled sulfidation before the annealing treatment. This progressive synthetic strategy causes the In2 O3 to be formed in situ on the In2 S3 to guarantee their intimate contact. This material shows high efficiency, good recyclability and excellent functional-group tolerability towards photocatalyzing the coupling of amines to imines. Experimental and density functional theory studies have verified that its highly enhanced photocatalytic performances are ascribed to its unique structural features. The synergistic effect of the β-In2 S3 /In2 O3 heterojunction with a tubular porous structure can enhance the absorption efficiency of broadband visible-sunlight. Upon being additionally coated with N-doped carbon, the intimately connected β-In2 S3 /In2 O3 interfaces can further improve the separation efficiency of photogenerated carriers.